2018
DOI: 10.1039/c8cp01949e
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio identification of the Li-rich phase in LiFePO4

Abstract: A recent discovery of anionic redox activity in Li-rich layered compounds opens a new direction for the design of high-capacity cathode materials for lithium-ion batteries. Here using extensive ab initio calculations, the thermodynamic existence of the Li-rich phase in LiFePO4 to form Li1+xFe1-xPO4 with x not exceeding 12.5% has been proved. Anionic redox activity and structural stability during delithiation are further investigated. Interestingly, it is found that Li1+xFe1-xPO4 cannot be delithiated completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 53 publications
1
33
0
Order By: Relevance
“…Plenty of studies have showed that DFT methods are becoming very useful, [35] and the Becke three-parameter functional with the Lee, Yang, and Parr correlation functional (B3LYP) [24] method is the most promising approach because it is very fast and sufficiently accurate for most problems. [2][3][4][5][6][7][8][9]34,[36][37][38][39][40][41][42] The B3LYP procedure is known to provide reliable geometries and frequencies. [36] Cedeño and Weitz [43] considered that the Becke88-Perdew86 exchange-correlation functional (BP86) [24,44] was the most reliable method for calculating the Fe-allyl bond enthalpy in both HFe(CO) 3 (η 3 -C 3 H 5 ) and IFe(CO) 3 (η 3 -C 3 H 5 ).…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Plenty of studies have showed that DFT methods are becoming very useful, [35] and the Becke three-parameter functional with the Lee, Yang, and Parr correlation functional (B3LYP) [24] method is the most promising approach because it is very fast and sufficiently accurate for most problems. [2][3][4][5][6][7][8][9]34,[36][37][38][39][40][41][42] The B3LYP procedure is known to provide reliable geometries and frequencies. [36] Cedeño and Weitz [43] considered that the Becke88-Perdew86 exchange-correlation functional (BP86) [24,44] was the most reliable method for calculating the Fe-allyl bond enthalpy in both HFe(CO) 3 (η 3 -C 3 H 5 ) and IFe(CO) 3 (η 3 -C 3 H 5 ).…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Nevertheless, the range of such data is somewhat limited, with emphasis found on weaker bonds in coordinatively saturated complexes. [1][2][3][4][5][6][7][8][9][10] Accurate quantum chemical calculations can give valuable information. The main advantage of using a theoretical method to study trends of bond strengths is that a systematically selected set of molecules can be studied without additional problems such as the appearance of instabilities.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations